Implementing Asynchronous Learning Activities in an EFL Speaking Classroom: Teachers' Strategies - Azzahra, Anugrah Syifa; Mobit, Mobit; Ridwan, Iwan (Journal of English Language and Education, 2023)
Teaching speaking during the pandemic has been an essential experience for the future situation. The aim of this research was to determine the strategy of EFL teachers in implementing asynchronous learning in speaking classes. The researchers used a narrative inquiry as the research design. It aims to obtain complete data and a comprehensive picture of how the teachers implement the asynchronous learning in speaking classroom. Data collection techniques was interviews and researchers used semi-structured interview as instrumentation. This research found that English teachers used to implement various strategies such as providing a suitable asynchronous platform, practicing dialogue, giving ideas or opinions, providing English learning videos, and singing a song, participants also explained that the strategies they used really helped them in carrying out speaking lessons in asynchronous classes. This research is expected to help teachers in choosing the right strategy for teaching speaking especially in asynchronous learning.